Edukasi Gizi Seimbang Remaja Untuk Cegah Stunting Dan Penyakit Kronik - Riska Rosita; Kresna Agung Yudhianto; Arsyita Putri Rahmatika; Tsasa Ristianingsih; Oktawiani Catur Widiasti (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
Adolescents have a crucial role in preventing stunting. The problems that occur at the Sukoharjo Health Vocational School are (1) the students' low level of knowledge about balanced nutrition and (2) the students' low health independence in adopting a healthy lifestyle. As a result, students experience iron deficiency (anemia), short height, thin or Chronic Energy Deficiency. Female students will be at risk of giving birth to stunted babies. The aim of this activity is to implement promotive and preventive efforts for balanced nutrition to prevent stunting and chronic diseases. The PkM method is promotive in the form of education about balanced nutrition, and preventive in the form of measuring LILA. The results of the activity show that many students now bring food from home so that their nutrition is more guaranteed. In addition, students are more orderly at breakfast so they can be more focused when learning activities take place. This is evident from the increasing assessment of student achievement.